Kegiatan Pengembangan Usaha Terhadap Usaha Es Noni di Desa Cijedil - Halim, Andrika Prakasa; Gunawan, Fransisca; Adirga, Giandre; Larisa, Gracia Tania; Christella, Jessy; Immanuel, Matthew; Rizky, Muhamad Reza; Gunawan, Sandy (Pusat Pengabdian kepada Masyarakat (PPKM) Universitas Prasetiya Mulya, 2019)
Es Noni is a home-based ice cream business that is still being classified as a small business as it needs a better development process to increase its sales. Therefore, Es Noni has several problems formulated from this case that needs to be solved. First, the production quantity of the ice cream was limited due to the absence of, no suitable freezer to store all of the production demand. Next, there was only one place to sell the ice cream continuously and they didn’t have a large, compatible cooling box that has enough space to store all of the sellable ice creams. Whereas the last problem is Es Noni never records its sales on a daily basis and their way of distributing the revenue is still incorrect. With all of the problems that Es Noni had, the author wanted to help in solving these problems. The author purchased most of the required equipment to increase the amount of production and sales. Moreover, the author discovered other sales methods to expand the ice cream’s market, alongside giving them the knowledge on how to write an accounting report correctly regarding their cash flow and product inventory to minimize the occurrence of adverse errors.